Dampak Status Sosial Ekonomi Orang Tua Terhadap Keterampilan Sosial Anak: The Impact of Parents' Socio-Economic Status on Children's Social Skills - Atika, Aisyah Nur; Rasyid, Harun (Pedagogia : Jurnal Pendidikan, 2018)
This research was conducted with the aim to analyze regression the influence of parental socioeconomic status on the social skills of 5-6 year olds in Malang Regency. This research was carried out in Kindergaten Karangploso District, Malang Regency. The time of the study was from March to April 2018. The data collection used Harry King's Nomograph method in determining the sample of the population. The total population of 645 with the standard error 5% with a multiplier factor of 1.195. The sample number was 200.1 rounded to 200 samples of the Harry King Nomograph method. Data analysis used the IBM SPSS 20 program. Based on the results of the study it was found there was a significant and positive influence on the parental socioeconomic status on the social skills of children aged 5-6 years in Malang Regency. The better and the higher of the parental socio-economic status, the higher the child's social skills. The implications of research results indicate that the parental socio-economic status can support children's development, so this can be used as a guide for parents to be able to give attention to their children both to the parents of low, middle and high. Governments, communities, teachers, and parents to collaborate and to encourage the spirit to the children.